Nitric oxide mediates angiogenesis in vivo and endothelial cell growth and migration in vitro promoted by substance P. - M Ziche; L Morbidelli; E Masini; S Amerini; H J Granger; C A Maggi; P Geppetti; F Ledda (The Journal of Clinical Investigation, 1994)
We evaluated the effects of nitric oxide (NO) generators and endogenous production of NO elicited by substance P (SP) in the angiogenesis process. Angiogenesis was monitored in the rabbit cornea in vivo and in vitro by measuring the growth and migration of endothelial cells isolated from coronary postcapillary venules. The angiogenesis promoted in the rabbit cornea by [Sar9]-SP-sulfone, a stable and selective agonist for the tachykinin NK1 receptor, and by prostaglandin E1 (PGE1), was potentiated by sodium nitroprusside (SNP). Conversely, the NO synthase inhibitor N omega-nitro-L-arginine methyl ester (L-NAME), given systemically, inhibited angiogenesis elicited by [Sar9]-SP-sulfone and by PGE1. Endothelial cells exposed to SNP exhibited an increase in thymidine incorporation and in total cell number. Exposure of the cells to NO generating drugs, such as SNP, isosorbide dinitrate, and glyceryl trinitrate, produced a dose-dependent increase in endothelial cell migration. Capillary endothelial cell proliferation and migration produced by SP were abolished by pretreatment with the NO synthase inhibitors N omega-mono-methyl-L-arginine (L-NMMA), N omega-nitro-L-arginine (L-NNA), and L-NAME. Exposure of the cells to SP activated the calcium-dependent NO synthase. Angiogenesis and endothelial cell growth and migration induced by basic fibroblast growth factor were not affected by NO synthase inhibitors. These data indicate that NO production induced by vasoactive agents, such as SP, functions as an autocrine regulator of the microvascular events necessary for neovascularization and mediates angiogenesis. Images